Tratamiento de leishmaniasis cutánea andina con ketoconazol en dos zonas de alta incidencia del Departamento de Amazonas: Reporte de Casos. - CABREJOS PITA, Jose Gabriel; LISIGURSKI TEITELMAN, Miriam; BRIONES GALLARDO, Jose; CASTAÑEDA OCAMPO, Williams; PAIMA MESTANZA, Kety Marilú; QUEZADA TIRADO, Eduardo (Revista Médica Herediana, 2013)
To report the use of Ketoconazole as alternative treatment for Andean Cutaneous Leishmaniasis (ACL) in two high incidence zones in Amazonas Department. Methods: It was considered patients with confirmed diagnosis of ACL whom there were difficulties for the administration of Pentavalent Antimonials. It was not considered patients below 2 years old, pregnant or nursing woman and patients with wounds bigger than 5 cm. diameter. Patients above 12 years old received Ketoconazole 600 mg. daily for 28 days; patients below 12 years old received only 200 mg. It was made clinical follow-up weekly during the treatment. There were treated 2 patients above and 2 patients below 12 years old. The two younger and one of the older had not been received any previous medical treatment, the other one had been received two previous courses of Glucantime®. The treatment was successful in the 4 cases. It was made clinical follow-up for 3 months in the younger patients and it was observed complete healing and absence of new lesions. Ketoconazole, 600 mg. daily for 28 days for below 12 years old patients and 200 mg. daily for above 12 years old patients could be considered an alternative treatment for ACL in Inguilpata and Yerbabuena Districts; in patients with or without previous Pentavalent Antimonials Treatments. ( Rev Med Hered 2002; 13: 144-147 )